PENGARUH EFEKTIVITAS KEPEMIMPINAN, KECERDASAN EMOSIONAL, DAN EFIKASI-DIRI TERHADAP KOMITMEN TUGAS PADA GURU SMTA PKP JAKARTA ISLAMIC SCHOOL - Sulaiman Ismail; Sulaiman W (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
The objective of this causal research was to obtain information concerning: (1) the effect of leadership effectiveness toward task commitment; (2) the effect of emotional intelligence toward task commitment; (3) the effect of self-efficacy toward task commitment; (4) the effect of leadership effectiveness toward self-efficacy; and (5) the effect of emotional intelligence toward self-efficacy.  The research was conducted by using a survey method with path analysis ini testing hypothesis. Ini this research, principals of  teachers on Senior High School PKP Jakarta Islamic School has been choosen as a unit analysis and 84 samples of principals were selected in random. The results of the research are as follows: (1) there is a direct positive effect of leadership effectiveness toward task commitment; (2) there is a direct positive effect of emotional intelligence toward task commitment; (3) there is a direct positive effect of self-efficacy toward task commitment; (4) there is a direct positive effect of leadership effectiveness toward self-efficacy; and (5) there is a direct positive effect of emotional intelligence toward self-efficacy.      Kata kunci:  efektivitas kepemimpinan, kecerdasan emosional, efikasi-diri, dan komitmen tugas